Penulisan Sastra Sebagai Upaya Pemajuan Literasi di SMA Negeri 1 Praya Lombok Tengah: BIOCOMPOS PRODUCTION BY UTILIZING CATTLE WASTE IN LENDANG NANGKA UTARA VILLAGE - Nuriadi, Nuriadi; Melani, Boniesta; Fitriana, Eka; Isnaini, Muh. (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Fertilizers are essential for the growth and development of plants, and one type of fertilizer is biocompost. Biocompost is an organic fertilizer that combines manure with charcoal chaff. Organic fertilizer is derived from dead animal parts, dung, and other organic waste. The northern village of North Lendang Nangka has a significant amount of potable waste that can be used as one of the ingredients for making biocompost, which is useful for land cultivation and increasing crop production. This activity aimed to utilize livestock waste as biocompost in the northern village of North Lendang Nangka. The methods used in this activity were socialization, biocomposting, quality testing, and packaging of biocompost. Biocomposting was done using an active ingredient to accelerate the composting process, the EM4 bioactive. As a result of the development of biocompost using raw materials from livestock waste and organic materials, people understand the effectiveness of the process used in the northern village of North Lendang Nangka and see that the levels of nitrogen, phosphorus, and potassium meet the quality of compost according to the SNI 19-7030-2004. The nitrogen in the compost was 0.38%, phosphorus was 0.69%, and potassium was 1.05%.